Inflation and public debt management. A time consistent approach - Antonello Eugenio Scorcu (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
The existence of long term or short term nominal ebt implies different dicretionary monetary policies. In absence of any monetization, long term debt leads to a lower inflation than short term debt. If debt monetization is possible, the lower inflation of long term case is traded off with the lower distortionary taxation in the short term case and no unambiguous conclusion can be reached.
Keywords: 330